The Gold Coast Leader (June 1905) - Gold Coast Leader (The Gold Coast Leader Office, Saltpond Road, Cape Coast, 1905)
The Gold Coast Leader was a weekly newspaper that reported on local, national, and international news, with an emphasis on colonial, political, and social issues affecting the Gold Coast.
Keywords: Gold Coast Leader Newspaper; History of Ghana